Different Obese Phenotypes and Progenitor Endothelial Cell Dysfunction: The Missed Link to Cardiovascular Risk - Berezin, A. E.; Березін, Олександр Євгенійович (Insight Medical Publishing, 2016)
Obesity has been remained a leading factor of metabolic and cardiovascular (CV) events worldwide. It has suggesting that obesity might effect on CV risk through several metabolic abnormalities including white adipose tissue and adipocytokines’ dysfunction, insulin resistance, impaired glucose metabolism and worsening of an endogenous repair system affected endothelial progenitor cells (EPCs). However, there are serious controversies regarding the level and functionality of EPCs in obese, metabolic syndrome, while EPCs dysfunction is considered a powerful risk factor of CV complications. By now, clinically use of EPC dysfunction as biomarker of altered endothelial function with high predictive ability to risk stratification in obese patients appears to be promised. The mini review is discussed differences in EPC between healthy obese and non-healthy people.
Keywords: Obese; Metabolically healthy obese; Stratification; Cardiovascular risk; Endothelial dysfunction; Endothelial progenitor cells